Pengembangan E-Portofolio Berbasis Web untuk Career Development Center - Fitriani, Leni; Setiawan, Ridwan; Hamdi, Wildan Hidayatul (Institut Teknologi Garut, 2024)
This research aims to develop an e-portfolio system for students and alumni of the Garut Institute of Technology, which is provided by the Career Development Center (CDC). This system allows users to archive digital work or proof of achievement which can be in the form of achievements, awards, certifications, work history, education, and involvement in organizations, as an e-portfolio. Agile methodology with a Scrum approach is used in this research, and this system is designed as a website using the React JS Framework. The result of this research is an alternative system that makes it easier for users to create and access e-portfolios digitally and helps the Career Development Center increase opportunities for students and alumni to find jobs that suit their skills and interests. This system allows users to manage and share e-portfolio results online or download them in pdf format.